2013
DOI: 10.1002/jgrd.50499
|View full text |Cite
|
Sign up to set email alerts
|

The lightning activity associated with the dry and moist convections in the Himalayan Regions

Abstract: Lightning activity in the dry environment of northwest India and Pakistan (NW) and in the moist environment of northeast India (NE) has been examined from the Optical Transient Detector and Lightning Imaging Sensor data obtained from the Tropical Rainfall Measuring Mission satellite during 1995–2010. In the NW region, seasonal variation of flash rate is annual with a maximum in July but is semi‐annual with a primary maximum in April and a secondary maximum in September, in the NE region. On diurnal scale, flas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…India shows the greatest seasonal and interannual variation. There is substantial evidence linking these variations in lightning activity to monsoon seasons (Kumar and Kamra, 2012;Pawar et al, 2012;Chaudhuri and Middey, 2013;Penki and Kamra, 2013). The ability of models to represent the monsoon as well as the links between the monsoon and lightning is important to consider when studying lightning in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…India shows the greatest seasonal and interannual variation. There is substantial evidence linking these variations in lightning activity to monsoon seasons (Kumar and Kamra, 2012;Pawar et al, 2012;Chaudhuri and Middey, 2013;Penki and Kamra, 2013). The ability of models to represent the monsoon as well as the links between the monsoon and lightning is important to consider when studying lightning in India.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be related to the occurrence of lightning in relation to other features of storms. It has been discussed in some papers that lightning peak months precede the rainfall peak months in monsoonal regions (Chaudhuri and Middey, 2013;Penki and Kamra, 2013). This may be relevant to variables such as convective rain and cloud-top height; however, one would expect the use of upward ice flux to begin to correct the delay.…”
mentioning
confidence: 99%
“…The monthly variation of lightning activity reveals that most of the regions other than northwest India (NW) show maximum lightning flash during pre-monsoon months (March-April-May). Maxima in lightning flash in NW region are found in the monsoon months (Penki and Kamra 2013). From various studies such as Kandalgaonkar et al (2005) and Ranalkar and Chaudhari (2009), it is established that spatiotemporal variability of lightning over Indian region is related to convective activity, large-scale circulation, land mass gradient and orography of that region.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southern Peninsula, the preferred time for occurrence of TS is 0900-1200 UTC (Litta and Mohankumar 2007). From the diurnal variability of flash rate in NW region, it is observed that low values of flash rate occur during morning hours, which increase by noon and remain high throughout the afternoon and early night (Penki and Kamra 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tibetan Plateau and steeper orography contribute to more vigorous updrafts leading to high cloud tops and enhanced lightning flashes in thunderclouds (Williams, 2001;Penki and Kamra, 2013). Kriplani and Kulkarni (1998) reported that the southwest monsoon carrying enormous quantities of moisture from the Bay of Bengal and orography of the region R 2 are the main cause of high precipitation.…”
Section: Lightning Convective Rainfall and Meteorological Parametermentioning
confidence: 99%